Interleukin-35-mediated induction of a novel regulatory T cell population - Collison, Lauren W. (2010)
Regulatory T cells (T(regs)) play a critical role in the maintenance of immunological self-tolerance. Naïve human or murine T cell treatment with the inhibitory cytokine IL-35 induces a regulatory population, termed iT(R)35, that mediates suppression via IL-35, but not IL-10 or TGFβ, neither express nor require Foxp3, are strongly suppressive in five in vivo models, and exhibit in vivo stability. T(reg)-mediated suppression induces iT(R)35 generation in an IL-35- and IL-10-dependent manner in vitro, and in inflammatory conditions in vivo in Trichuris-infected intestines and within the tumor microenvironment, where they appear to contribute to the regulatory milieu. iT(R)35 may constitute a key mediator of infectious tolerance, may contribute to T(reg)-mediated tumor progression, and ex vivo generated iT(R)35 may possess therapeutic utility.